Pertumbuhan Ekonomi Sebagai Cerminan Perkembangan Perekonomian Suatu Negara - Ivonia Auxiliadora Freitas Marcal; Yosse Putra Oentoro; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Economic growth is the main indicator that reflects the economic development of a country. Through economic growth analysis, it can be seen how economic policy, investment, productivity and other factors contribute to an increase or decrease in gross domestic product (GDP) and social welfare. This article reviews the concept of economic growth, its determining factors, and its implications for the country's economy. Apart from that, various challenges faced in efforts to achieve sustainable and inclusive economic growth are also discussed. By understanding the dynamics of economic growth, policymakers can design effective strategies to encourage stable and sustainable economic development.